A new sign allowing diagnosis in the pathologies of the extensor tendons of the hand. Issue 6 (June 2018) - Leti Acciaro, A.; Pilla, F.; Colzani, G.; Corradi, N.
Abstract: Introduction: The thorough knowledge of the anatomy of the extensor tendon system of the hand is crucial for clinical examination and detection of tendon injuries. The Juncturae between the EDCII and other extensor tendons presents different incidences, shapes ("r" or "y") and morphologies (Type I, II, III). The EIP does not receive connection. These characteristics may result in variable effects on extensor tendons during active finger movements. The purpose of this study is to investigate and describe a new sign helping diagnosis for injuries or pathologies of EIP and EDC index finger (EDC II), based on a cadaveric dissection and clinical observation. Materials and methods: The authors performed a clinical observational study in 520 patients in order to distinctly evaluate by means of inspection and palpation the EIP and EDC II tendons and an anatomical analysis of extensor tendon apparatus of long fingers was then performed in 89 cadaver hands focusing the investigation on the juncturae system. Results: The observational studies showed that during the flexion of the III, IV and V fingers, associated to the active extension of the I and II fingers, the EDC of the III, IV and V fingers moved the EDC II in ulnar direction by means of juncturae action. The EIP remained in its position becoming visible and isolated from the migrated EDC II. Conclusions: This feature allows the distinct clinical evaluation by observation and palpation of both EDC II and EIP tendons and may be helpful in clinical conditions such as diagnosis of tendon lesions, pre-operative planning of EIP transfer and extensor tendon tenolysis associated to soft tissue scar at the second MPj.